2021
DOI: 10.20944/preprints202104.0531.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omics in Major Cereals: Applications, Challenges, and Prospects

Abstract: Omics technologies, viz., genomics, transcriptomics, proteomics, metabolomics, and phenomics, are becoming an integral part of virtually every commercial cereal breeding program because they provide substantial dividends per unit time in both pre-breeding and breeding phases. Continuous advances in cereal-omics promise—in combination with time efficiency—the cost benefits. In this review, we provide a comprehensive overview of the established cereal-omics methods in five major cereals, viz.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 116 publications
(153 reference statements)
0
9
0
Order By: Relevance
“…These results suggest that the SA, JA, protein phosphatases and MAPK-WRKY signaling pathways are the central metabolic pathways activated in response to aphid attack and can be targeted for aphid tolerance breeding. Thus, transcriptomic analysis has become central in abiotic and biotic stress tolerance studies (Li et al, 2019;Kaur et al, 2021; Table 3), and genes and metabolic pathways identified in these studies can be used as targets in marker assisted breeding programs. With the large amount of data that has been generated and deposited into various public repositories, it is now possible to conduct meta-analysis of transcriptomic responses to abiotic and biotic stresses.…”
Section: Transcriptomicsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggest that the SA, JA, protein phosphatases and MAPK-WRKY signaling pathways are the central metabolic pathways activated in response to aphid attack and can be targeted for aphid tolerance breeding. Thus, transcriptomic analysis has become central in abiotic and biotic stress tolerance studies (Li et al, 2019;Kaur et al, 2021; Table 3), and genes and metabolic pathways identified in these studies can be used as targets in marker assisted breeding programs. With the large amount of data that has been generated and deposited into various public repositories, it is now possible to conduct meta-analysis of transcriptomic responses to abiotic and biotic stresses.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Thus, GWAS improves the mapping resolution for accurate location of allele/QTL/genes underlying key agronomic traits ( Huang and Han, 2014 ; Pang et al, 2020 ). Unsurprising, large-scale GWAS has become a powerful tool for performing efficient genome-phenotype association analysis and identification of causative QTL/genes for key agronomic traits in diverse crop species ( Sun et al, 2017 ; Jha et al, 2020 ; Berhe et al, 2021 ; Kaur et al, 2021 ; Sinha et al, 2021 ). For instance, using a natural population comprising 713 upland cotton accessions, Sun et al (2018) discovered a total of 10 and 15 SNPs that were significantly associated with relative survival rate and salt tolerance level, respectively, among which two SNPs (i46598Gh and i47388Gh) on genomic region D09 were simultaneously linked with the two traits.…”
Section: Genomics and Pan-genomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mRNA enrichment was performed by using poly-T attached magnetic beads, followed by enzymatic fragmentation. The paired-end (PE) sequencing libraries were prepared by using the Illumina TrueSeq stranded mRNA Sample Preparation Kit (Illumina Inc., San Diego, CA, USA) (Kaur et al, 2021). The purification of ds cDNA samples was performed by using Ampure XP beads, followed by A-tailing, adapter ligation, and further enrichment by PCR.…”
Section: Rna Sequencing (Rna Seq)mentioning
confidence: 99%